PENGARUH JARAK ALUR TERHADAP KESTABILAN ALIRAN FLUIDA BERDENYUT DALAM SALURAN BERPENAMPANG SEGIEMPAT - Prayitno Ciptoadi (ALE Proceeding, 2018)
The pulsatile fluid flow in a transverse grooved channel would become self-sustained oscillatory flow at a certain critical Reynold number. The critical Reynold number where laminar unsteady flow changed to unsteady transitional one depends on grooves distances. The objective of this research is to analyze the effect of grooves distances toward the vortex strength and the stability of the fluid flow. This research was done by implementing a closed square cross-section channel, where the bottom surface of the channel was semicircle grooved. The frequency of flow oscillation measurement was done by setting up a resistance manometer and measurement was done at several Reynold numbers. From the research result, it is seen that the largest vortex strength occurs at the smallest groove distance. The flows become instability in all of the grooves distances by seen Phase Plane.